Complications in the study of ancient tuberculosis: non-specificity of IS6110 PCRs. Issue 1 (6th January 2015) - Müller, Romy; Roberts, Charlotte A.; Brown, Terence A.
Abstract : The insertion sequence IS6110 is frequently used as a marker for the presence of ancient DNA (aDNA) derived from bacteria of the Mycobacterium tuberculosis complex (MTBC) in human archaeological remains. The specificity of polymerase chain reactions (PCRs) directed at IS6110 has, however, been questioned, because identical or similar elements have been identified in 'mycobacteria other than tuberculosis (MOTT)'. These are Mycobacterium species, common in the environment, which may occasionally cause opportunistic diseases and are not normally associated with clinical cases of tuberculosis (TB). We report the presence of two sequence types that are similar, but not identical, to IS6110 in bone samples from nine skeletons dated mainly to the Roman period, one from Scotland and the others from the remainder of Britain. The sources of these sequences cannot be established but they are most likely derived from environmental bacteria that have colonised the skeletons after death. The data presented support the notion that IS6110 may not be unique to the members of the MTBC and is, therefore, not suitable as a specific marker for the identification of TB in human remains. Statement of significance: Individuals who suffered from tuberculosis in the past can sometimes be identified by examining archaeological skeletons for the presence of DNA from the bacteria that cause the disease. Often the DNA that is searched for is a sequence called IS6110, which is thought to be present only in the Mycobacterium tuberculosis family of bacteria. If the IS6110 sequence is detected in a bone or tooth then that individual must have been infected with tuberculosis bacteria. This test has been used frequently since the 1990s to identify tuberculosis in archaeological remains, but we show that it is not accurate. Sequences similar to IS6110 are also present in other bacteria, including ones that live in soil and which might get into a bone or tooth while the skeleton is buried. The IS6110 test should not therefore be used to detect archaeological tuberculosis unless accompanied by other tests that are more specific.